MMHub, a database for the mulberry metabolome. (11th March 2020) - Li, Dong; Ma, Bi; Xu, Xiaofei; Chen, Guo; Li, Tian; He, Ningjia
Abstract: Mulberry is an important economic crop plant and traditional medicine. It contains a huge array of bioactive metabolites such as flavonoids, amino acids, alkaloids and vitamins. Consequently, mulberry has received increasing attention in recent years. MMHub (version 1.0) is the first open public repository of mass spectra of small chemical compounds (<1000 Da) in mulberry leaves. The database contains 936 electrospray ionization tandem mass spectrometry (ESI-MS 2 ) data and lists the specific distribution of compounds in 91 mulberry resources with two biological duplicates. ESI-MS 2 data were obtained under non-standardized and independent experimental conditions. In total, 124 metabolites were identified or tentatively annotated and details of 90 metabolites with associated chemical structures have been deposited in the database. Supporting information such as PubChem compound information, molecular formula and metabolite classification are also provided in the MS 2 spectral tag library. The MMHub provides important and comprehensive metabolome data for scientists working with mulberry. This information will be useful for the screening of quality resources and specific metabolites of mulberry. Database URL: https://biodb.swu.edu.cn/mmdb/